2016
DOI: 10.1167/tvst.5.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Gaussian Mixture-Model With Expectation Maximization for Detecting Glaucomatous Progression in Standard Automated Perimetry Visual Fields

Abstract: PurposeTo validate Gaussian mixture-model with expectation maximization (GEM) and variational Bayesian independent component analysis mixture-models (VIM) for detecting glaucomatous progression along visual field (VF) defect patterns (GEM–progression of patterns (POP) and VIM-POP). To compare GEM-POP and VIM-POP with other methods.MethodsGEM and VIM models separated cross-sectional abnormal VFs from 859 eyes and normal VFs from 1117 eyes into abnormal and normal clusters. Clusters were decomposed into independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 33 publications
(37 reference statements)
0
45
0
Order By: Relevance
“…Several studies have employed progression of patterns 13 and unsupervised Gaussian mixture-models 14,15 on VF data. OCT has not been utilized to its full extent when training model machine learning based on OCT information.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have employed progression of patterns 13 and unsupervised Gaussian mixture-models 14,15 on VF data. OCT has not been utilized to its full extent when training model machine learning based on OCT information.…”
Section: Discussionmentioning
confidence: 99%
“… 42 , 43 In the present study, as we approximately knew the anticipated number of resultant classes for VF test location assignment, 18 , 44 we applied the ISODATA algorithm. As a further point of contrast with the work described by previous authors, which identified clusters of VFs, such as patterns of VF loss, 14 17 application of clustering in the present study was to identify clusters of VF spatial test locations that is facilitated by the use of satellite imaging algorithms. Finally, the statistical rigidity of the classification is tested using the D T statistic.…”
Section: Methodsmentioning
confidence: 69%
“…Other studies have used cluster analysis to identify patterns of VF defects appearing in patients with glaucoma both cross-sectionally 12 , 14 , 41 and to detect progression. 15 17 In contrast to studies using mixture of Gaussian models, 15 17 k means presents a stricter class assignment for a particular datum point with the assumption that the point is highly certain to belong the assigned class, while a mixture of Gaussian incorporates a degree of uncertainty into class assignment. Their utility has been debated in the literature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Yousefi et al. ). Simulation models of glaucoma progression have been developed to evaluate the cost‐effectiveness of frequent testing in patients with glaucoma (Boodhna and Crabb ) as well as to evaluate different treatment strategies (Van Gestel et al.…”
Section: Case Study Of Glaucomamentioning
confidence: 99%